Severe fever of Carrion - Odriozola, Ernesto (1921)
Carrion's fever, or severe fever Carrion is the most interesting chapter of the disease we are studying. Very dark data we have about the nature, etiology, symptoms and ways to combat it, have been and continue to be serious doubts and hottest controversies.